PERANCANGAN MITIGASI BAHAYA DAN RISIKO KECELAKAAN KERJA PADA PRODUKSI SARUNG TANGAN GOLF DI PT CAHAYA PERADA ABADI - Phanjaya, Visakha
PT Cahaya Perada Abadi (PT CPA) is a manufacturing company in the textile industry, primarily producing golf gloves. This study focuses on the Q3 type golf gloves, which constituted approximately 68% of the total glove production in 2023. The production process of golf gloves includes stages such as cutting, preparation, subassembly, assembly, finishing, and ends with final quality control. At PT CPA, there is no historical data on the mapping of occupational health and safety (OHS) risks, even though this information is crucial for the company to consider suitable work activities and environments. Initial interviews also revealed frequent workplace accidents, such as needle pricks during sewing and body aches due to non-ergonomic working conditions. Therefore, the company has stated the need for an evaluation of risk levels at PT CPA to reduce potential hazards.